Ayurvedic Management of Gridhrasi W.S.R. Lumbago SciaticaSyndrome with “Pippali Churna Vati” - Sahoo, Kabita Kumari; Khuntia, Bipin Bihari (International Research Journal of Ayurveda & Yoga, 2025)
Gridhrasi (Sciatica) one of the important disorders affecting the locomotors system is increasing day by day in present scenario. It (sciatica) is one among the Vataja Nanatmaja Vyadhi (disease) described in Ayurveda which is the most common disorders caused by Vata and is very difficult to manage in clinical practice. Gridhrasi is said to cause an abnormal throwing action in the affected leg. By this abnormality and due to the persisting severe pain, the patient has a typical gait (slightly titled toward the affected side and affected leg in slightly flexed position whereas other leg is extended) resembles with the gait of vulture, and hence, the name Gridhrasi is given to this unique illness. A case of a 45-year-old man experiencing pain in lower back region radiating to right leg since 8 months. Patient also had complaints of stiffness, tingling sensation, and numbness in his right lower limb since 6 months. Hence, he administered trial drug “Pippali Churna vati”(Pippali churna, Eranda Taila, and Gomutra), 2 g twice in a day (Morning and Evening) followed by luke warm water for 3 months. (Follow-up in each 30 days). The symptoms of Gridhrasi (Sciatica) like Ruka (Pain), Toda (Pricking Sensation), Stambha (Stiffness), and Spandan (Twitching), Kaphaja symptoms like Aruchi (Anorexia), Tandra (Drowsiness), and Gaurava (Heaviness), and tests such as S.L.R. test and walking test were observed over the treatment. Analysis of result showed improvement in Gridhrasi (Sciatica). Study concluded that given treatment is found effective in management of Gridhrasi.